ANALISIS YURIDIS PENYELESAIAN PERMASALAHAN PEWARISAN HUKUM ADAT BATAK TOBA ATAS SISTEM KEKERABATAN PATRILINEAL - Musyafah, Aisyah Ayu; Sabila, Salsa (Justitia et Pax, 2026)
Customary inheritance law in the Batak Toba community is closely related to the patrilineal kinship system, which traditionally places sons as successors of lineage, family property, and customary responsibilities. However, social change, judicial development, and the principle of equality under Indonesian law have influenced the position of daughters in inheritance disputes. This article aims to analyse the inheritance system in Batak Toba customary law and examine the legal position of women in Batak Toba inheritance under Indonesian positive law. This research uses a normative juridical method with statutory, conceptual, and case approaches. The findings show that Batak Toba inheritance practice cannot be understood as a uniform rule that absolutely excludes women from inheritance. Although the patrilineal structure traditionally prioritises sons, women may obtain property through grants, Pauseang, family agreement, or judicial recognition. Supreme Court decisions have also contributed to the recognition of inheritance rights for daughters and widows. This article argues that resolving Batak Toba inheritance disputes requires a model of harmonisation between customary values and Indonesian positive law, particularly by distinguishing women’s legal entitlement to inheritance from customary grants or family-based compensation.